PENGELOLAAN KNOWLEDGE MANAGEMENT CAPABILITY DALAM MEMEDIASI DUKUNGAN INFORMATION TECHNOLOGY RELATEDNESS TERHADAP KINERJA PERUSAHAAN - Ifada, Luluk Muhimatul (Jurnal Akuntansi dan Keuangan Indonesia, 2011)
The study examines whether or not and how information technology (IT) relatedness influences corporate performance. This study proposes that knowledge management (KM) is a critical organizational capability through which IT influences firm performance. Measurement of IT relatedness and KM capability uses a reflective second-order factor modeling approach for capturing complementarities among the four dimensions of IT relatedness (IT strategy making processes, IT vendor management processes, IT human resource management processes and IT infrastructure) and for capturing complementarities among the three dimensions of KM capability (product KM capability, customer KM capability, and managerial KM capability). A survey was conducted among 93 branch managers of banking in Central Java. Structural Equation Model (SEM) was used to analyze the data using the software program of SmartPLS (Partial Least Square). The findings support for the hypotheses of the study. IT relatedness of business units enhances the cross unit KM capability of the corporate. The KM capability creates and exploits cross-unit synergies from the product, customer, and managerial knowledge resources of the corporate. These synergies increase the corporate performance. IT relatedness of business units positively influences corporate performance. IT relatedness also has significant indirect effects on corporate performance through the mediation of KM capability.